2021
DOI: 10.1002/eji.202048580
|View full text |Cite
|
Sign up to set email alerts
|

Human type 1 and type 2 conventional dendritic cells express indoleamine 2,3‐dioxygenase 1 with functional effects on T cell priming

Abstract: Dendritic cells (DCs) are key regulators of the immune system that shape T cell responses. Regulation of T cell induction by DCs may occur via the intracellular enzyme indoleamine 2,3‐dioxygenase 1 (IDO), which catalyzes conversion of the essential amino acid tryptophan into kynurenine. Here, we examined the role of IDO in human peripheral blood plasmacytoid DCs (pDCs), and type 1 and type 2 conventional DCs (cDC1s and cDC2s). Our data demonstrate that under homeostatic conditions, IDO is selectively expressed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 52 publications
(79 reference statements)
0
12
0
Order By: Relevance
“…It has been recently reported that cDC1 express IDO1, and TLR ligation further increases IDO1 expression in cDC1s, whereas induces only modest expression in cDC2s ( Sittig et al., 2021 ). To exploit the pattern of IDO1 expression in human cDCs, cDC1 and cDC2 were isolated from human PBMCs from healthy donors, and IDO1 expression was measured after LPS treatment.…”
Section: Resultsmentioning
confidence: 99%
“…It has been recently reported that cDC1 express IDO1, and TLR ligation further increases IDO1 expression in cDC1s, whereas induces only modest expression in cDC2s ( Sittig et al., 2021 ). To exploit the pattern of IDO1 expression in human cDCs, cDC1 and cDC2 were isolated from human PBMCs from healthy donors, and IDO1 expression was measured after LPS treatment.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, unlike cDC1s, cDC2s are not as potent at cross-presentation; however, are the most abundant population in lymphoid and non-lymphoid tissues [ 299 ] and are better activators of human CD4 + T cells than cDC1s [ 292 ], thereby increasing the priming CD4 + T cells [ 299 , 300 ]. Recently, it has been reported that human cDC2 (also cDC1) can negatively induce the functional effects on T cell priming by IDO expression [ 301 ].…”
Section: Dual Effect Of Immune Cells In Cancermentioning
confidence: 99%
“…Another tolerogenic DC feature is the expression of the inhibitory receptor immunoglobulin-like transcript (ILT)-3, which has been associated with the increased generation of Tregs ( 46 , 49 , 51 , 52 ). Furthermore, immunoregulatory enzymes can be upregulated by tolerogenic DCs, such as indoleamine-2,3-dioxygenase (IDO), which leads to a decreased T-cell proliferation and the induction of Tregs ( 53 55 ). Taken together, compared to immunogenic DCs, tolerogenic DCs are generally characterized by lower expressions of CD80/86, MHCII, and IL-12, while they secrete TGF-β and IL-10 and express tolerogenic markers such as PD-L1, ICOSL, ILT-3, and IDO.…”
Section: Dcs As Inducers Of Peripheral Tolerancementioning
confidence: 99%